Tinjauan Yuridis Pasal 59 Peraturan Pemerintah Nomor 35 Tahun 2021 Mengenai Ketentuan Pesangon Bagi Pekerja UMKM Berdasarkan Asas Perlindungan Pekerja - Rindi Putri Afifah; Didha Narin Aiza; Ikhsan Romansah Gawi (CV Rewang Rencang, 2021)
The Job Excogitation Law is implemented by the Government of Indonesia with the aim of creating the widest possible employment, protection of MSMEs, increased investment, and protection of worker welfare. However, the law gave rise to polemics, one of which related to termination of employment on severance money, especially in the derivative rules in Article 59 of Government Regulation No. 35 of 2021. It is mentioned that for MSME entrepreneurs, the amount of severance is given based on worker agreements with employers. It looks vague and contrary to the Principle of Worker Protection because it opens the opportunity for unilateral severance money determination by employers.